Exploration of Empathy-Based Leadership in the Context of Employee Retention in the Creative Industry - Sugiarto, Irwan (PT. LITERASI SAINS NUSANTARA, 2024)
The creative industry often faces high pressure and tight deadlines, making a work environment that supports employees' psychological well-being crucial. Empathy-based leadership is seen as an approach that can create harmonious relationships between leaders and employees, which in turn can enhance employee retention in a highly dynamic and competitive environment. This study focuses on exploring empathy-based leadership in the context of employee retention in the creative industry, a sector characterized by high demands for innovation, flexibility, and creativity. This study uses a literature review method with a qualitative approach. The data used in this research is taken from Google Scholar within the publication range of 2012-2024. The study results show that empathy-based leadership has a significant impact on improving employee retention in the creative industry. By understanding and responding to the emotional and professional needs of employees, empathetic leaders can create a supportive, inclusive, and collaborative work environment. This is particularly important in the creative industry, where high work pressure and innovation are key to success. Examples from various companies such as Kreavi, Agate International, and Pixar show that empathetic leadership can reduce turnover rates, increase employee satisfaction and engagement, and foster innovation.